1992
DOI: 10.1128/iai.60.2.606-611.1992
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter mustelae isolation from feces of ferrets: evidence to support fecal-oral transmission of a gastric Helicobacter

Abstract: Helicobacter mustelae has been isolated from stomachs of ferrets with chronic gastritis and ulcers. When H. mustelae is inoculated orally into H. mustelae-negative ferrets, the animals become colonized and develop gastritis, a significant immune response, and a transient hypochlorhydria. All of these features mimic Helicobacterpylori-induced gastric disease in humans. Because the epidemiology of H. pylori infection is poorly understood and its route of transmission is unknown, the feces of weanling and adult f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…H. mustelae transmission to the kits occurred near the time of weaning from contact with their naturally infected jills obtained from a colony in which H. mustelae is endemic. The fecal-oral route was the most probable mode of transmission, because fecal shedding of H. mustelae was noted in several jills in this study and has been documented previously [34]. Earlier studies indicated that kits become naturally colonized with H. mustelae near weaning [4], a finding that is supported by observations that kits begin leaving the nest box after 3 weeks of age, thus allowing for a greater exposure to feces and subsequent risk of fecal-oral transmission of H. mustelae.…”
Section: Discussionsupporting
confidence: 81%
“…H. mustelae transmission to the kits occurred near the time of weaning from contact with their naturally infected jills obtained from a colony in which H. mustelae is endemic. The fecal-oral route was the most probable mode of transmission, because fecal shedding of H. mustelae was noted in several jills in this study and has been documented previously [34]. Earlier studies indicated that kits become naturally colonized with H. mustelae near weaning [4], a finding that is supported by observations that kits begin leaving the nest box after 3 weeks of age, thus allowing for a greater exposure to feces and subsequent risk of fecal-oral transmission of H. mustelae.…”
Section: Discussionsupporting
confidence: 81%
“…When H. mustelae is inoculated orally into H. mustelae-free ferrets, the animals become colonized and develop gastritis, as well as a significant immune response and transient hypochlor-hydria [10]. Following infection, H. mustelae can be isolated from ferret feces [11]. Isolation of H. mustelae from feces appears to correspond to periods of transient hypochlorhydria [11].…”
Section: Introductionmentioning
confidence: 99%
“…Following infection, H. mustelae can be isolated from ferret feces [11]. Isolation of H. mustelae from feces appears to correspond to periods of transient hypochlorhydria [11]. In addition, increased frequency of isolation of H. mustelae from the feces corresponds to drug-induced hypochlorhydria [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is now known that H. mustelae colonizes nearly 100% of ferrets shortly after weaning. Feces from weanling and adult ferrets have been screened for the presence of H. mustelae to determine whether fecal transmission could explain the 100% prevalence observed in weanling and older ferrets (Fox et al, 1988b(Fox et al, , 1992b. Helicobacter mustelae was isolated from the feces of 8 of 74 nine-week-old and 3 of 8 eight-month-old ferrets.…”
Section: Helicobacter Mustelaementioning
confidence: 99%